Pengembangan Video Pembelajaran Berbasis Animasi untuk Meningkatkan Minat dan Motivasi Belajar Siswa SMP - Akbar, Anisa; Marniati, Marniati; Subawo, Made (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a valid, practical, and effective animation-based learning video for mathematics subjects in grade VIII of junior high school to increase students' interest and motivation to learn. The method used is the development research method (Research and Development [PT5.1]) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 30 grade VIII students of Muhammadiyah Pomalaa Junior High School. The research instruments were in the form of expert validation sheets, student response questionnaires, and learning interest and motivation questionnaires. The results showed that the validity level of material experts was 81% with a very valid category and media experts was 77.86% with a valid category. The practicality level was 81.57% with a very practical category. The effectiveness of the media was shown by an increase in learning interest from 47% to 90% and learning motivation from 30% to 87%. Thus, the animation-based learning video developed was proven to be valid, practical, and effective and was able to increase students' interest and motivation to learn in accordance with the research objectives. Keywords: ADDIE, Animation, Interest, Motivation, Learning Videos.